2020
DOI: 10.1515/pp-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Two vs. three weeks of treatment with amoxicillin-clavulanate for stabilized community-acquired complicated parapneumonic effusions. A preliminary non-inferiority, double-blind, randomized, controlled trial

Abstract: Two vs. three weeks of treatment with amoxicillin-clavulanate for stabilized community-acquired complicated parapneumonic effusions. A preliminary non-inferiority, double-blind, randomized, controlled trial Abstract Background: The optimal duration of antibiotic treatment for complicated parapneumonic effusions (CPPEs) has not been properly defined. Our aim was to compare the efficacy of amoxicillin-clavulanate for 2 vs. 3 weeks in patients with CPPE (i.e. those which required chest tube drainage). Methods: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…A randomized controlled trial (RCT) on patients with complicated parapneumonic effusion who were stable after 2 weeks of antibiotic treatment reported that a 2-week course was probably no inferior to a 3-week course in terms of treatment failures. 66 However, this study did not include patients with primary pleural infection and was unable to recruit the total planned number of participants.…”
Section: Treatmentmentioning
confidence: 99%
“…A randomized controlled trial (RCT) on patients with complicated parapneumonic effusion who were stable after 2 weeks of antibiotic treatment reported that a 2-week course was probably no inferior to a 3-week course in terms of treatment failures. 66 However, this study did not include patients with primary pleural infection and was unable to recruit the total planned number of participants.…”
Section: Treatmentmentioning
confidence: 99%
“…The median duration of antimicrobial treatment was 26 days in our study. Except for one trail that was terminated early due to slow enrolment, the optimal duration of antimicrobial treatment has not been examined in randomized controlled trials [21]. Most guidelines recommend individualised treatments durations of three weeks, depending on clinical improvement, and one trail is ongoing to validate this [6].…”
Section: Discussionmentioning
confidence: 99%
“…13 Based on expert opinions, antibiotics should be continued for at least 3 weeks, though in selected less severe cases, 2 weeks may be enough. 17…”
Section: Management Of Pleural Infectionsmentioning
confidence: 99%
“…Conversely, TT failed in 17% of patients, thus requiring additional invasive procedures, but IPC succeeded in all. The study was underpowered due to slow enrollment and had two remarkable and interrelated facts that may complicate its interpretation: the larger mean fluid drainage in the IPC group (17,412 vs. 2,901 mL) and the low mean rate of additional thoracentesis (1.3) required in the TT group within the study period. The greater volume of drained fluid probably explained the lower concentrations of serum albumin in the IPC group at 12 weeks (27 vs. 32.5 g/L).…”
Section: Indwelling Pleural Cathetersmentioning
confidence: 99%